Prospective cohort study exploring the neurodevelopmental outcomes following documented neonatal sepsis in Nepal: study protocol - Manu Raj; Remya Sudevan; Swechhya Vaidya; Jayasree Chandramathi; Shailendra Bir Karmacharya; Kalpana Subedi; Ganendra Bhakta Raya; Dhruba Shrestha (BMJ Paediatrics Open)
Introduction Neonatal sepsis, a significant contributor to global neonatal mortality, poses substantial risks to infant health, particularly in low-resource countries like Nepal. Despite its high prevalence, there is a lack of clarity in defining and understanding neonatal sepsis, leading to challenges in diagnosing and managing the condition effectively. The probable impact of neonatal sepsis on long-term neurodevelopmental outcomes, including motor and cognitive delays, remains under-explored in Nepal. The primary objective of this study is to report the prevalence of neurodevelopmental delay in neonates with documented sepsis. The secondary objective is to report significant associations of the same with selected probable risk factors.Methods and analysis This is a dual-centric prospective cohort study that is ongoing at two hospitals—Paropakar Maternity and Women’s Hospital and Siddhi Memorial Hospital in Nepal, over a 2-year period. Neonates diagnosed with sepsis will be assessed using the Developmental Assessment Scale for Indian Infants at 6 months and 1 year, postdiagnosis. Statistical analyses will include prevalence estimation and logistic regression.